Synchronizing learning material on Moodle and lecture based supportive tool: The REST based approach - Kautsar, I. A.; Musashi, Y.; Kubota, S. I.; Sugitani, K. (2015 International Conference on Information Communication Technology and Systems (ICTS), 2015)
A lecturer's role are the important part for the success of any eLearning platform, include Moodle LMS. Because only lecturers that enrich learning materials. Unfortunately, Indonesia still faces the bandwidth gap that made difficulties to use Moodle as a daily basis. Moreover, it will become complex when lecturer decide to install it on a local machine. This paper presents supportive tool that not only for enrich learning materials in offline conditions with easy initiation steps, but also synchronize it on remote LMS using Moodle RE ST web service in order to share learning material in limited bandwidth.
Keywords: Decision support systems; Hafnium; Information and communication technology; Moodle; Moodle LMS; Moodle REST Web service; REST; REST-based approach; Supportive Tool; Web Service; Web services; bandwidth gap; e-Learning platform; learning management systems; learning material; remote LMS; synchronisation; synchronization